The Crisis of Scientific Publications in Religious Universities: The Transformation of Tri Dharma Implementation to Penetrate Superior Accreditation - M. Alhabsyi, Ni’ma; Muh. Natsir Mahmud; Syamsuddin; Hasyim Haddade; Petta Solong, Najamuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study analyzes the crisis of scientific publications in the Islamic Religious Education Study Program (PAI) IAIN Sultan Amai Gorontalo with a focus on transforming the implementation of the Tri Dharma of Higher Education to support the achievement of superior accreditation. The research uses a qualitative method with a case study design. Data were collected through document desk reviews, observations, in-depth interviews, and Focus Group Discussions (FGDs), then analyzed using the Miles and Huberman models. The results of the study show that Sinta-accredited national publications have increased by 15% per year, while reputable international publications have decreased from 8 articles (2022 and 2023) to 2 articles (2024). The variation in productivity between lecturers is quite high, influenced by limited facilities, publication costs, lack of collaboration, and evaluation oriented towards the quantity of training. This study contributes a conceptual framework of the relationship between causal factors, outcomes, and action strategies. Recommendations include target-based mentoring, special funding for publications, strengthening global research networks, and outcome-based evaluation.